What Went Wrong: Corona and the World after the Full Stop. (21st July 2020) - Caduff, Carlo
Abstract: This article examines the global response to the Covid‐19 pandemic. It argues that we urgently need to look beyond the virus if we want to understand the real seriousness of what is happening today. How did we end up in a space of thinking, acting, and feeling that has normalized extremes and is based on the assumption that biological life is an absolute value separate from politics? The author suggests that today's fear is fueled by mathematical disease modeling, neoliberal health policies, nervous media reporting, and authoritarian longings.